Penyusunan Indeks Keberlanjutan Sistem Ketersediaan Beras di Indonesia Tahun 2021 - Asnuri, Sari; Yuliana, Rita (Politeknik Statistika STIS, 2023)
Rice as the main food of the Indonesian people plays an important role in the sustainability of the population. The increasing demand for rice over time and the increasingly complex problems in agriculture require to create sustainable rice availability. To evaluate the sustainability achievements in rice availability system, a measure is needed that can describe the sustainability of rice availability. This study aims to develop a sustainability index of the rice availability system by using a composite index method using 34 indicators divided into five dimensions, namely ecology, economy, socio-culture, institutions, and technology. The results show that there are 19 provinces that have moderately sustainable rice availability, and 15 provinces are less sustainable.. Each province has a different performance, indicated by the various scores of the dimensions of the rice availability index. The resulting rice availability sustainability index is able to describe the food sufficiency condition of a region, indicated by the correlation between the rice availability index and the food security index. In addition, there is a negative correlation between the rice availability index and the real wage of farm laborers.